"How Can I Trust People When They Know Exactly What My Weakness Is?" Daily Life Experiences, and Resilience Strategies of Stateless Afghans in Iran - Farahani Hadi; Langari Maliheh Nekouei Marvi; Eliasi Laleh Golamrej; Tavakol Mohamed; Toikko Timo (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This study aimed to explore the daily life experiences of stateless Afghans in Iran and to describe their resilience strategies that enabled them to manage life deprivations. Using narrative analysis, we interviewed 34 individual stateless Afghans in Iran. Four main themes were identified in their daily life experiences: ignored as nonexistent, second-class Muslims, institutional discrimination, and unpredictability of the future. In terms of resilience strategies, three main themes emerged: cohesive community support, the role of religion, and ideological exploitation. Policy improvements are suggested to decrease discrimination and law amendments to provide a legal presence for Afghans residing in Iran.